Study on stable configurations and snap through of the rectangular VS bi-stable laminates with curvilinear fiber alignment - Wu, C.C.; Hao, Y.X.; Zhang, W. (Composite structures, 2025)
With advances in fiber placement technology, variable stiffness bistable laminates (VSBL) composited by curvilinear fiber format become a subject of intense interest for morphing structures due to their lower weight, adjustable stiffness and a richer range of stable configurations compared to straight fiber bistable laminate. Merely conducting research on square laminates is not enough allowing for practical application scenarios. This article investigates the influence of geometrical parameters of VSBL on the stable state configuration and static snap through actuated by MFC systematically. A quadratic variable curvature polynomial is used to fit the transverse displacement according to classical laminate theory. By means of von-Karman geometrical relationship and the Rayleigh-Ritz method, stable configurations of the VS bistable laminate are solved. By comparing with finite element results, the reliability and precision of the current results are verified. It shows that changing fiber orientation leads to significant effects on the steady state configuration and critical bifurcation points. Theoretical analysis of VS bistable laminates containing the smart piezoelectric material MFC is followed by analytical modeling. The voltage threshold required for actuating snap through of two stable states is acquired by smart material layer MFC. The specific reasons for the differences in the configurations of VS bistable laminates are illustrated by analyzing distribution of the stiffness of VSBL in the plane.